Peste des petits ruminants Control Programme and Strategies in India: Current Scenario - V. Balamurugan; K. Vinod Kumar; G. Govindaraj; Parimal Roy (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Peste des petits ruminants (PPR) is an acute, highly contagious, OIE notifiable and economically important transboundary viral disease of sheep and goats. PPR is enzootic in India as a greater number of outbreaks have occurred in the past and now occurring regularly round the year and throughout the country. The PPR outbreaks in sheep and goats have declined in some of the Indian states Viz., Andhra Pradesh, Telangana, Karnataka, and Chhattisgarh after implementing the strategic mass vaccination campaigns. The decreased number of outbreaks, as well as changes in the disease severity patterns and distribution, might be due to the effectiveness of the vaccine, timely vaccination, and most importantly effective implementation of the vaccination strategic plan. This review is focused upon the overall understanding of the National PPR Control Programme (PPR -CP) and its strategies vaccination implantation in India for the control and eradication of PPR.